Public Sector Audit as a Provider of High-Quality Information on Activity of the Governments - MURATBEKOVA, Zhazira; AINABEK, Kuandyk; DAVLETBAYEVA, Nazgul (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
Article presents a research of methodology of the public sector audit providing formation of high-quality information on activity of the governments for its subsequent assessment. The governments have few incentives for disclosure of accurate and transparent information. Effective methods of the public sector audit have to promote increase in the accountability of executive power, transparency of the budgetary processes and, as a result, improvement of an assessment of activity of government. The importance of work is defined to justification of need of involvement of the public sector audit in an assessment of reliability of the reporting of executive authorities, efficiency of the budgetary procedures, by need of introduction of modern methods of the reporting of state bodies on the basis of the analysis of world practice, the relevant institutional structure of the public sector audit, to definition of spheres of further improvement of activity of bodies of the public sector audit. The International practice presented in article regarding theoretical and methodological bases, can be applied with success in the Republic of Kazakhstan in case of its creative transformation, with its obligatory legal and methodological adaptation to conditions of our country. Increase in transparency of the budgetary processes will become the major step to increase in efficiency of activity of public authorities.